2003
DOI: 10.1159/000073122
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation after Acoustic Tumour Resection in Neurofibromatosis Type 2: Impact of Intra- and Postoperative Neural Response Telemetry Monitoring

Abstract: The present paper reports about a 16-year-old male with neurofibromatosis type 2 (NF-2) of the Wishart type with bilateral deafness who had undergone cochlear implantation after resection of the acoustic neuroma (AN) of the same side. Neural response telemetry (NRT) recordings are essential in those patients during cochlear implantation where no stapedial reflexes can be electrically elicited due to the resection of the AN. In the present case, amplitude growth function and a type II pattern of the NRT wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the 1990s, Cueva [1992] reported on auditory sensations elicited by electrical promontory stimulation (EPS) in a patient with preserved cochlear nerve and deafness after VS resection, demonstrating the theoretical feasibility of cochlear implantation in deafened NF2 patients with intact cochlear nerve after VS removal. Since then, histological [Belal, 2001] and clinical studies Hulka et al, 1995;Tono et al, 1996;Graham et al, 1999;Ahsan et al, 2003;Nolle et al, 2003;Aristegui and Denia, 2005] confirmed that cochlear implantation is possible in at least a subset of this special population of patients. Today, we can offer 2 options for hearing restoration, cochlear or auditory brainstem implantation, to NF2 deafened patients with an anatomically preserved cochlear nerve.…”
Section: Introductionmentioning
confidence: 88%
“…In the 1990s, Cueva [1992] reported on auditory sensations elicited by electrical promontory stimulation (EPS) in a patient with preserved cochlear nerve and deafness after VS resection, demonstrating the theoretical feasibility of cochlear implantation in deafened NF2 patients with intact cochlear nerve after VS removal. Since then, histological [Belal, 2001] and clinical studies Hulka et al, 1995;Tono et al, 1996;Graham et al, 1999;Ahsan et al, 2003;Nolle et al, 2003;Aristegui and Denia, 2005] confirmed that cochlear implantation is possible in at least a subset of this special population of patients. Today, we can offer 2 options for hearing restoration, cochlear or auditory brainstem implantation, to NF2 deafened patients with an anatomically preserved cochlear nerve.…”
Section: Introductionmentioning
confidence: 88%
“…Again, this technique is limited to tumours of <15 mm in the cerebellopontine angle, unless there is a subtotal resection. There were 13 papers in total in this group with 16 ears who had retrosigmoid surgery and five ears in the group that had had middle fossa surgery . Useful data were available in all but one case.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There were 13 papers in total in this group with 16 ears who had retrosigmoid surgery and five ears in the group that had had middle fossa surgery. 50,64,65,68,[72][73][74][75][76] Useful data were available in all but one case.…”
Section: Failed Hearing Preservation Surgery and Cochlear Implant Omentioning
confidence: 99%
“…Cueva et al 5 elicited auditory sensation through electrical promontory stimulation in 6 patients with NF2 who underwent tumor removal with cochlear nerve preservation. Since then, about 31 cases of cochlear implantation in NF2 patients have been reported in the literature 6 7 8 9 10 11 12 13 14 15 16 . The timing of implantation varied from simultaneously to 10 years after tumor resection.…”
Section: Discussionmentioning
confidence: 99%